Hastening Potassium Release from Mica Waste by Treating Humic Substrate Solution: An Approach to Adopt Mica Waste as Potassium Amendment in Tea-growing Soil. Issue 15 (22nd August 2019) - Pramanik, Prabhat; Kalita, Chayanika; Borah, Krishna
ABSTRACT: Muriate of potash (MoP) is generally applied in soil for supplementing potassium (K) in agricultural soil; though MoP has some disadvantages as K-fertilizer especially under humic agro-climatic condition. In this context, mica waste (MW) could be a potential alternative for K supplementing in soil. However, slow K-releasing nature limits its application as K source in agricultural soil. In this study, humic substrates (HS) were externally applied along with MW for hastening its rate of K release in soil. Application of HS and MW combination significantly ( P < .05) increased K availability in soil. A pot study revealed that the combination of HS with even half of the recommended K in the form of MW sustained plant growth and recorded at par exchangeable K content in soil as compared to recommended MoP treatment. The scanning electron microscopy and x-ray diffraction revealed the changes in the crystal structure of HS-treated MW, and that might be attributed to the enhanced release of K from MW. Based on the observations, it could be concluded that application of HS at 7.5 kg HS ha −1 hastened K release from MW to support the plant growth even after supplementing half of the recommended amount of K through MW. This controlled experiment established the potential of HS-treated MW as an alternative K source in agricultural soil. However, it also implied that a field experiment is necessary to optimize the combination of MW and MoP as an integrated K management treatment for a specific agroclimatic condition.